2007
DOI: 10.1177/0003319706291112
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac Calcification Is a Marker of Generalized Atherosclerosis

Abstract: Aortic valve calcification (AVC) and carotid artery calcification (CAC) are considered to be markers of generalized atherosclerosis. However, the role of intracardiac calcification (ICC) (valvular and perivalvular calcification) is unclear. The objective of this retrospective study was to analyze the relationship between ICC and CAC, risk factors, and clinical atherosclerotic disease. Risk factors included age, sex, diabetes mellitus, hypercholesterolemia, and hypertension; clinical atherosclerosis comprised s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…In asymptomatic AS, advanced AVC is a strong predictor of poor prognosis, with increased risk of death and aortic valve replacement (Rosenhek et al ., ). Moreover, numerous studies have shown an association between AVC and adverse clinical events (Rosenhek et al ., , ; Pohle et al ., ; Branch et al ., ; Nemcsik et al ., ; Palmiero et al ., ; Ishii et al ., ; Corciu et al ., ; Pradelli et al ., ). Recently, AVC assessment by TEE has been shown useful in transcatheter aortic valve implantation procedures for predicting postprocedural aortic regurgitation (Colli et al ., ; Koos et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In asymptomatic AS, advanced AVC is a strong predictor of poor prognosis, with increased risk of death and aortic valve replacement (Rosenhek et al ., ). Moreover, numerous studies have shown an association between AVC and adverse clinical events (Rosenhek et al ., , ; Pohle et al ., ; Branch et al ., ; Nemcsik et al ., ; Palmiero et al ., ; Ishii et al ., ; Corciu et al ., ; Pradelli et al ., ). Recently, AVC assessment by TEE has been shown useful in transcatheter aortic valve implantation procedures for predicting postprocedural aortic regurgitation (Colli et al ., ; Koos et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Aortic valve calcification (AVC) is considered an active disease process of the aortic valve associated with risk factors and molecular pathways that lead to disease progression and, eventually, complications (Otto, ). Moreover, AVC is a powerful predictor of adverse clinical events for patients with cardiac (Pohle et al ., ; Palmiero et al ., ; Corciu et al ., ; Pradelli et al ., ) and vascular diseases (Rossi et al ., ), and in the general population (Rosenhek et al ., , ; Pohle et al ., ; Branch et al ., ; Nemcsik et al ., ; Palmiero et al ., ; Ishii et al ., ; Corciu et al ., ). AVC has also been recognized as a risk factor for complications after transcatheter aortic valve implantations (Colli et al ., ; Koos et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Large calcifications of the aortic valve for example, may lead to impaired leaflet function followed by heart failure [ 30 ]. Calcifications of the mitral annulus are part of a chronic non-inflammatory degenerative process [ 32 ], and severe calcifications of the mitral annulus may cause mitral regurgitation [ 31 ]. Therefore, cardiac valve calcifications should be reported in the clinical radiology routine where individual risk factors may be unknown [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…В последние годы этой патологии уделяется особое внимание, что обусловлено не только негативным влиянием прогрессирующего кальциноза на гемодинамические характеристики клапана. В ряде исследований показано, что кальциноз аортального клапана связан с сердечно-сосудистым риском, наличием сахарного диабета и системного атеросклероза [15][16][17][18]. В этой связи обсуждается общность патогенетических механизмов кальциноза аортального клапана с атеросклерозом сосудов [19,20].…”
Section: таблица 3 структурно-функциональные изменения миокарда у боunclassified